Kulturasi Agama dan Budaya dalam Struktur Pemerintahan Kerajaan Balanipa Abad 17 - 18 - Lutfiah Ayundasari; Muh. Farrel Islam (Tsaqofah dan Tarikh: Jurnal Kebudayaan dan Sejarah Islam, 2021)
In the pre-Islamic era in the archipelago, a traditional state had existed with its distinctive and varied system of government. In balanipa kingdom as one of the superior kingdoms in the confederation of Pitu Ulunna Salu and Pitu Babana Binanga, developed a governmental structure based on the social state of its people. Post-penetration of Islamic culture, balanipa kingdom accommodates Islam in its governance structure by giving a special position to ulama in the efforts to enforce Islamic sharia. The purpose of this research is to describe the transformation of the governance structure of the Kingdom of Balanipa XVII – XVIII Century. This research relies on the use of credible primary and secondary data with historical methods. The results of this study show that Islam is accommodated in the governance structure of the Kingdom of Balanipa through a position in a customary structure called Kali. In this position, Kali acts as an enforcer of Islamic law.